Perkembangan Peluang dan Tantangan Wisata Halal di Aceh (Jurnal Adabiya, 2020)
The tourism sector is one sector that is able to increase employment and economic growth. Currently, halal tourism (halal tourism) is starting to be in great demand. This is in line with the increase in Muslim tourists from year to year. The development of halal tourism has begun to be carried out by various countries, both Muslim and non-Muslim majority countries. One of the things that come to mind when people call Aceh is the application of Islamic Shari'a in every aspect of life, including the aspect of tourism. Halal tourism is an ongoing effort by the Acehnese Government to realize the Aceh brand as a halal symbol. The fact is that Aceh won three categories in the 2016 National Halal Tourism Competition held by the ministry of Tourism of Republic of Indonesia. Aceh's tourism potential is very promising both in terms of diversity and unique culture, culinary peculiarities, coffee flavors, atmosphere in the coffee shop, Islamic culture and its natural and beautiful natural charm. Efforts to branding Aceh as halal tourism are challenges that are not easy to implement. The halal label in Aceh is actually not a terminology that needs to be debated again. This article will explore the development of halal tourism in Aceh, review the concepts and principles of halal tourism, and discuss opportunities and challenges
Keywords: Halal tourism; Muslim tourist; chance; challenge